The Effects of Plasma Exosomes of Young Individuals Compared to Old Ones on Age-Related Inflammation and Lineage Differentiation of CD34+ Umbilical Cord Blood Hematopoietic Stem Cells - Helali, Maryam; Kaviani, Saeid; Alizadeh, Shaban; Afrisham, Reza; Ahmadvand, Mohammad (Current Topics in Medicinal Chemistry, 2025)
IntroductionCellular aging is a complicated event known for gradually reducing homeostasis, leading to a higher susceptibility to diseases and mortality. Since the behavior of Hematopoietic Stem Cells (HSCs) is potentially affected by plasma-derived exosomes, this study aimed to investigate whether the plasma-derived exosome of young and elderly human donors can deliver “youth” or “aging” signals into human umbilical cord blood-derived HSCs in vitro.MethodsExosomes were isolated from four young (Y-exo) and four old (O-exo) donors. Umbilical cord blood-derived HSCs were exposed to two concentrations of exosomes (5 and 10 μg/mL). Then, lineage differentiation (CD41 and CD38), the mRNA and protein expression of IL-1β and IL-6, and NFκB activity were evaluated using flow cytometry, qRT-PCR Enzyme-Linked Immunosorbent Assay (ELISA) methods, and western blot techniques, respectively.ResultsThe lineage-specific markers CD41 and CD38 expression were increased after exposure to O-exo compared to Y-exo at the concentration of 10 μg/mL (P<0.001). The HSCs treated with 10 μg/mL O-exo increased protein and mRNA expression of IL-1β and IL-6 compared to Y-exo at 10 μg/mL concentration (P<0.01). Furthermore, a significant difference was seen in p-NF-κB levels between O-exo and Y-exo at the concentration of 10 μg/mL (P=0.0014).ConclusionOur findings advocated the concept that circulating exosomes of old and young individuals may differently affect the pathways involved in the aging process in HSCs.Therefore, exosomes may be applied as therapeutic agents for regenerative medicine.
Keywords: hematopoietic stem cells